2000
DOI: 10.1017/s0012162200000542
|View full text |Cite
|
Sign up to set email alerts
|

Explicit memory in low-risk infants aged 19 months born between 27 and 42 weeks of gestation

Abstract: The aim of this study was to determine whether there are primary effects of prematurity on the development of explicit memory. Elicited imitation of action sequences was used to compare immediate and 15-minute delayed memory in term and preterm infants (19 months corrected age; n=48) who were at low risk: none had experienced the medical or social risk factors often associated with preterm birth. Relative to infants born at term (38 to 40 weeks' gestation), children who had been born at 27 to 34 weeks' gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Both term and preterm HI populations show heightened incidence for an array of cognitive and behavioral deficits, including language impairments [32,33,35,36,37,109,110], attentional problems associated with ADHD [42,43,44,45,46,47,54,63,111] and memory impairments [33,38,39,40,56,57,64,112,113]. In the current series of studies, we focus specifically on working memory impairments associated with neonatal HI injury in a rat model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both term and preterm HI populations show heightened incidence for an array of cognitive and behavioral deficits, including language impairments [32,33,35,36,37,109,110], attentional problems associated with ADHD [42,43,44,45,46,47,54,63,111] and memory impairments [33,38,39,40,56,57,64,112,113]. In the current series of studies, we focus specifically on working memory impairments associated with neonatal HI injury in a rat model.…”
Section: Resultsmentioning
confidence: 99%
“…This emphasis reflects the fact that memory impairments are an extremely common outcome in clinical HI populations, and may relate to poor academic achievement, as well as lower IQ scores in childhood [55,56,57,102,103,104,107]. HI-associated memory impairments may also co-occur with additional disabilities, for example in executive functioning and/or attention [51,52,57,64,65,67,105,106,112,113]. Overall, memory deficits appear to form a core impediment to educational success for neonatal HI populations.…”
Section: Resultsmentioning
confidence: 99%
“…Although this difference is not surprising (given that optimal management of the diabetic pregnancy is to deliver between 37 and 38 weeks; see Nold & Georgieff, 2004), previous research with slightly older infants has suggested that memory performance may vary as a function of gestational age (see de Haan et al, 2000); therefore, this variable was entered as a covariate in all elicited imitation analyses. Since these results suggested differences in global cognitive functioning between the two groups, individual's MDI scores were also entered as a covariate in the analyses of elicited imitation performance in an attempt to isolate explicit memory performance from general cognitive ability.…”
Section: Preliminary Analysesmentioning
confidence: 98%
“…There is now reason to think that some of these later deficits may have their roots in infancy. First, studies of information processing in the first year of life have found preterms to be slower at encoding information than full-terms, and to have poorer recognition memory, recall memory, and attention (de Haan, Bauer, Georgieff, & Nelson, 2000;Miranda & Fantz, 1974;Rose, 1980Rose, , , 1983Rose, Feldman, & Jankowski, 2001Sigman & Parmelee, 1974;Spungen, Kurtzberg, & Vaughan, 1985). Second, the newer infant information processing abilities have been found to predict IQ and language in later childhood and early adolescence (Colombo, Shaddy, Richman, Maikranz, & Blaga, 2004;Dougherty & Haith, 1997;Fagan, 1984;Fagan & Haiken-Vasen, 1997;Fagan & McGrath, 1981;McCall & Carriger, 1993;Rose & Feldman, 1995;Rose, Feldman, & Jankowski, 2003a;Sigman, Cohen, Beckwith, Asarnow, & Parmelee, 1991;Thompson, Fagan, & Fulker, 1991).…”
mentioning
confidence: 99%